Cover dan Kata Pengantar Jurnal Pendipa Vol.2 No.3 Edisi Oktober 2018 - Jurnal Pendipa (PendIPA Journal of Science Education, 2018)
Cover dan Kata Pengantar Jurnal Pendipa Vol.2 No.3 Edisi Oktober 2018